The curriculum for the Rural Education in the context of national legislation - Cleide Carvalho de Matos; Genylton Odilon Rêgo da Rocha (Universidade Federal do Norte do Tocantins, 2020)
The present research presents an analysis of the curricular prescriptions for the rural education in Brazil considering the educational legislations. Its objective is to understand the political, economic and social relations and their reverberations in the curricular prescription for the rural education. The study was carried out through bibliographical and documentary research. The documents analyzed were: Organic Law of Primary Education - Decree-Law No. 8,529 / 46, Organic Law of Agricultural Education - Decree-Law No. 9.613 / 46, Brazilian Educational Laws and Guidelines 4.024 / 61; Law 5.692 / 71 and Law 9.394 / 96, the Operational Guidelines for Basic Education in Rural Schools - DOEBEC - CNE / CEB Resolution Nº. 1 - April 3, 2002 and Complementary Guidelines for Basic Rural Education - Resolution CNE / CEB 2/2008. We found that the curriculum designed for rural areas - although regulated by the same norms as those for urban populations - has specificities that differentiate it, since the educational practice planned to rural areas has as its intentionality the insertion of students in productive work.